The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/ijms22020742
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Angiopoietin-Like Proteins and Adipose Tissue: Another Piece of the Relationship between Adiposopathy and Cardiometabolic Diseases?

Abstract: Angiopoietin-like proteins, namely ANGPTL3-4-8, are known as regulators of lipid metabolism. However, recent evidence points towards their involvement in the regulation of adipose tissue function. Alteration of adipose tissue functions (also called adiposopathy) is considered the main inducer of metabolic syndrome (MS) and its related complications. In this review, we intended to analyze available evidence derived from experimental and human investigations highlighting the contribution of ANGPTLs in the regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 114 publications
(163 reference statements)
0
20
0
Order By: Relevance
“…ANGPTL3 can significantly inhibit the phospholipase activity of endothelial lipase, resulting in reduced plasma HDL-protein hydrolysis [ 17 ]. ANGPTL3 can specifically bind to adipocytes and promote the release of fatty acids and glycerol from adipocytes to the liver, where they are further converted into triglycerides and glucose, resulting in an increase in the content of free fatty acids in the plasma [ 4 , 18 ]. Recent studies have also revealed that ANGPTL3 and ANGPTL8 interact synergistically to significantly enhance the inhibition of LPL activity [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…ANGPTL3 can significantly inhibit the phospholipase activity of endothelial lipase, resulting in reduced plasma HDL-protein hydrolysis [ 17 ]. ANGPTL3 can specifically bind to adipocytes and promote the release of fatty acids and glycerol from adipocytes to the liver, where they are further converted into triglycerides and glucose, resulting in an increase in the content of free fatty acids in the plasma [ 4 , 18 ]. Recent studies have also revealed that ANGPTL3 and ANGPTL8 interact synergistically to significantly enhance the inhibition of LPL activity [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Statins, which inhibit the synthesis of cholesterol in the liver, lower LDL-C more than non-HDL-C and relatively more than the molar quantity of ApoB [28] , indicating that reduction of cholesterol is not sufficient to control the hepatic secretion of all the ApoB-containing lipoproteins. Elegant Mendelian randomization studies that mimic the effects of CETP inhibitors and statins, by combining variants in the cholesterol ester transfer protein (CETP, in charge of exchanging cholesterol between VLDL and high density lipoproteins) and the 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR, the rate limiting step enzyme for cholesterol synthesis) genes (to create genetic scores) robustly affirmed the relevance in targeting ApoB, as a unique direct marker of both LDL and liver-derived VLDL and remnants [29] . In fact, a CETP score at or above the median was associated with lower levels of LDL-C, lower ApoB, and consistently lower CVD risk.…”
Section: Liver-derived Lipoproteins As Potent Cardiovascular Risk Pre...mentioning
confidence: 95%
“…However, the effect of both scores together was additive for LDL-C but not for ApoB or CVD risk. Indeed, the reduction of LDL-C in people harboring both scores equated to the sum of each independent score, although the extent of the reduction in ApoB and CVD risk were attenuated in people harboring both scores vs. those achieved by a single score [29] . Thus, Mendelian randomization indicates that the primary mechanism of benefit from lowering LDL-C relates to the lowering of the number of LDL particles, i.e., to the lowering of ApoB.…”
Section: Liver-derived Lipoproteins As Potent Cardiovascular Risk Pre...mentioning
confidence: 98%
“…ANGPTL3 is a known inhibitor of LPL and favors the dietary triglycerides to be stored in adipose tissue during feeding [47,48]. Homozygous loss-of-function mutations in ANGPTL3 are responsible for a phenotype that is known as familial hypobetalipoproteinemia type 2 (FHBL2) (OMIM #605019).…”
Section: Evinacumabmentioning
confidence: 99%